Pengaruh Konten Akun Instagram @exploretangerang terhadap Pemenuhan Kebutuhan Informasi Destinasi Wisata Kuliner - Haq, Rafi; Khairani, Aulian; Yoman, Mad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research is entitled "The Influence of Using the Instagram Account @exploretangerang on Fulfilling the Information Needs of Tourist Destinations." The formulation of the problem that will be discussed in this research is whether there is an influence and how much influence the use of the Instagram account @exploretangerang has on fulfilling the information needs of tourist destinations. The aim is to find out how much influence the @exploretangerang Instagram account has on fulfilling the information needs of tourist destinations. The theory used is the uses and gratification theory. The method used is a quantitative method using a purposive sampling technique. The results of the research show that the use of social media has a positive and significant effect on information needs. Based on the results of the coefficient of determination test, it was found that media use (X) had an influence on fulfilling information needs (Y) while the remainder was influenced by other factors not examined in this research.